Uterine exteriorization versus intraperitoneal repair in primary and repeat cesarean delivery: a randomized controlled trial. (1st February 2022) - Mohr-Sasson, Aya; Castel, Elias; Lurie, Irina; Heifetz, Sigal; Kees, Salim; Sivan, Eyal
Abstract: Purpose: The aim of this study is to evaluate the effect of uterine exteriorization versus intraperitoneal repair, in first compared to repeat cesarean delivery. Methods: A prospective randomized control single-blinded trial conducted in a single tertiary center between March 2014 and March 2015, including 32 and 63 women in first and recurrent cesarean sections, respectively. Inclusion criteria were elective operation and gestational age ≥37 weeks. Operative outcomes were compared between the groups including mean operative time, blood loss, hypotension, perioperative nausea and pain. Post-operative outcomes were further compared, including post-operative analgesia demand, first recognized bowel movement, nausea, length of hospital stay, fever, endometritis surgical site infection rate, and total satisfaction. Results: During the study period, 45 and 50 women were designated for uterine exteriorization and intraperitoneal uterine repair, respectively. Mean blood loss was 452 cc (±10.44) for the extraperitoneal compared to 540 cc (±29.83) for the intraperitoneal uterine repair group ( p  = .004). No other significant differences in either intraoperative or postoperative complications were demonstrated in and between the groups. Conclusion: Intraperitoneal repair of uterine incision is associated with higher operative blood loss compared to uterine exteriorization. No other differences in operative and postoperative complication rates were found between the groups.